Perforated Gastric Diverticulum in a Preterm Newborn: A Case Report - Seyed Amir Kazem Vejdan; Malihe Khosravi; Zahra Amirian (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2020)
Gastric diverticulum in newborn infants is the rarest (0.04%) of gastrointestinal diverticula. Most of them especially in this age group are asymptomatic or cannot be diagnosed based on examinations and symptoms. However, if it becomes symptomatic, the symptoms can range from vague abdominal pain to bleeding, perforation or torsion. The present case report discusses a preterm newborn with a perforated gastric diverticulum.